Transformación digital para una gestión eficiente y sostenible en la Facultad de Administración, Finanzas e Informática de la Universidad Técnica de Babahoyo: hacia un campus inteligente y conectado. - Márquez Mora, Julissa Briggitte (2025)
The case study focuses on the digitalization process of the Faculty of Administration, Finance and Informatics of the Technical University of Babahoyo, which is advancing on the path towards a digital, intelligent and connected campus. The need for modernization of teaching and administration is highlighted to offer better efficiency, accessibility and sustainability to the faculty. The work focuses on the analysis of the use of emerging technologies such as automation, data mining and the Internet of Things, which would allow resources to be better managed and the quality of education improved. This project does not attempt to immediately implement the digital transformation but rather to offer important information and propose lines of action for future improvement plans. Similarly, emphasis is placed on the importance of an adequate analysis to find opportunities for improvement, their potential benefits and the dangers that may arise. An introduction of digital platforms that can improve processes for teaching and research is also expected in accordance with the offering of desirable and desirable resources for the reality of the current educational context. The central idea is to move towards an interconnected campus model, which promotes innovation and allows more efficient decisions to be made within the framework of a growing digital environment.